Special aspects of the transformation of the Russian tax system in contemporary conditions - Denis N. Putimtsev; Elena V. Ordynskaya (RUDN Journal of Public Administration, 2024)
Taxation problems are traditionally relevant. Currently, this issue is becoming even more relevant due to the need to transform the Russian tax system, considering the need to ensure sustainable economic development. The issues of tax reform for both individuals and legal entities are considered by many researchers, however, some aspects have not been sufficiently studied and covered in the specialized scientific literature. In particular, the presented work examines the possibilities of using tax incentives to involve individuals more actively in investment processes. Proposals for the implementation of these measures are presented. The research also discusses some of the most relevant areas of tax administration that need to be actively developed in the near future.